Geospatial semantics and the semantic Web foundations, algorithms, and applications - Ashish, Naveen; Sheth, Amit P.; SpringerLink (Online service). (Boston Springer, 2011)
The availability of geographic and geospatial information and services, especially on the open Web has become abundant in the last several years with the proliferation of online maps, geo-coding services, geospatial Web services and geospatially enabled applications. The need for geospatial reasoning has significantly increased in many everyday applications including personal digital assistants, Web search applications, local aware mobile services, specialized systems for emergency response, medical triaging, intelligence analysis and more. Geospatial Semantics and the Semantic Web: Foundations, Algorithms, and Applications, an edited volume contributed by world class leaders in this field, provides recent research in the theme of geospatial semantics. This edited volume presents new information systems applications that have potential for high impact and commercialization. Also, special effort was made by the contributors to focus on geospatial ontology development, related standards, geospatial ontology alignment and integration, and algorithmic techniques for geospatial semantics. Case studies and examples will be provided throughout this book as well as possibilities for future research.
Representing and Utilizing Changing Historical Places as an Ontology Time Series -- Semantic Referencing of Geosensor Data and Volunteered Geographic Information -- SPARQL-ST: Extending SPARQL to Support Spatiotemporal Queries -- Spatial Cyberinfrastructure: Building new pathways for geospatial semantics on existing infrastructures -- Ontology-Based Geospatial Approaches for Semantic Awareness in Earth Observation Systems -- Location-Based Access Control Using Semantic Web Technologies -- Topographic Mapping Data Semantics Through Data Conversion and Enhancement.
Electronic reproduction.
Keywords: Geographic information systems; Semantic Web; Electronic books